Impacts of Indonesian Economic Growth: Remittances Migrant Workers and FDI - Ukhtiyani, Khairah; Indartono, Setyabudi (JEJAK: Jurnal Ekonomi dan Kebijakan, 2020)
This study aims to identify: (1) the effect of remittance of Indonesian workers on Indonesia's economic growth from 1998-2018; (2) the effect of Foreign Direct Investment on Indonesia's economic growth from 1998-2018; and (3) the effect of remittances of Indonesian workers and Foreign Direct Investment (FDI) on Indonesia's economic growth from 1998-2018. Based on previous studies found differences in the results of contributions. This study uses a quantitative model using remittances from Indonesian workers and FDI as independent variables, and the dependent variable is economic growth. The population of this study is all secondary data about the percentage of GDP and FDI remittances and the level of economic growth in Indonesia in 1998-2018. Tests conducted are prerequisite tests for multicollinearity, heteroscedasticity, autocorrelation, and multiple regression hypothesis testing using SPSS 21 to measure the effect of independent variables on the dependent variable partially and simultaneously. The results of this study stated that there was no significant effect on the remittance of Indonesian workers and FDI on Indonesia's economic growth from 1998-2018 because the receipt of remittances by Indonesian workers was used by households for food consumption and expenditure, not for investment or to open businesses. Meanwhile, Indonesia's FDI bureaucracy is still inefficient and there is a need for infrastructure development to increase foreign investor interest. In addition, Indonesia is still oriented towards imports rather than exports.